Politik Kebijakan Infrastruktur: Tinjauan Pustaka Kebijakan Infrastruktur Transportasi - Nora Eka Putri (Faculty of Social Science, Universitas Negeri Padang, 2020)
This study examined the conceptualization of public policy consisting of public policy concepts, public policy models; Public policy process; Policy actor; Transportation infrastructure policy. Through this article it will be known the role of the policy actor in giving birth to public policy especially the transportation infrastructure policy. The actor's role will help in the success and/or failure of a policy in the field of transportation infrastructure. This was a literature study. Data in this study were collected through reviewing the literature from various sources such as googlescholar.com; sciencedirect.com and other relevant sources. The literatures that were referenced came from a variety of published years and from various policy issues that came from various countries. The conclusion of this writing was that the public policy and policy actor were very urgent and had important role of in childbirth infrastructure policy especially in the field of transportation. In the future, this article becomes a conceptual reference for interested parties to examine the issue of policy actor role in formulating public policy.